1998
DOI: 10.1046/j.1365-2036.1998.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of food and acid reflux in patients with low‐grade oesophagitis—the role of an anti‐reflux agent

Abstract: Patients with grades I and II oesophagitis reflux food and acid independently, and are predominantly either food refluxers or acid refluxers, but not both. Liquid alginate decreases the number of both food and acid reflux events, but does not change their duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
5
25
0
Order By: Relevance
“…Although the inhibition of gastric acid secretion is known to decrease the time that the oesophageal pH < 4, 8,[36][37][38] gastric acidity has received limited attention with respect to its potential underlying role in oesophageal acid exposure in GERD. [39][40][41][42][43][44][45] The present finding that cisapride decreases post-prandial oesophageal acid exposure in subjects with GERD agrees with previous findings by others, [11][12][13][14][15] who have attributed this action of cisapride to its motility effects on the lower oesophageal sphincter pressure, oesophageal peristalsis and gastric emptying. [11][12][13][14][15] Our present results, however, indicate that the decrease in oesophageal acidity can be explained by a cisapride-induced decrease in gastric acidity.…”
Section: Discussionsupporting
confidence: 93%
“…Although the inhibition of gastric acid secretion is known to decrease the time that the oesophageal pH < 4, 8,[36][37][38] gastric acidity has received limited attention with respect to its potential underlying role in oesophageal acid exposure in GERD. [39][40][41][42][43][44][45] The present finding that cisapride decreases post-prandial oesophageal acid exposure in subjects with GERD agrees with previous findings by others, [11][12][13][14][15] who have attributed this action of cisapride to its motility effects on the lower oesophageal sphincter pressure, oesophageal peristalsis and gastric emptying. [11][12][13][14][15] Our present results, however, indicate that the decrease in oesophageal acidity can be explained by a cisapride-induced decrease in gastric acidity.…”
Section: Discussionsupporting
confidence: 93%
“…In vivo, the alginate raft forms within a few minutes of drug administration and, by floating on top of the gastric contents, preferentially moves into the esophagus during episodes of GOR in place of the acidic gastric contents, thus effectively reducing the likelihood of mucosal damage [9][10][11][12]. Since the raft can be retained on top of the stomach contents for several hours, alginate-based raft-forming formulations can provide longer-lasting relief compared to antacids [7][8][9][10][11][12][13][14]. Therefore, the present study was aimed at comparing sodium alginate and magaldrate, a reference antacid, with respect to symptom relief efficacy, not only in terms of the extent of overall symptom relief but also in terms of the speed and duration of action and safety.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with GORD, it has been shown that alginate-containing preparations reduce the frequency and severity of symptoms [6,7], decrease the number of both food and acid reflux events [8], and limit the proximal migration of refluxed material [7]. Antireflux properties of alginates are based on the interaction with gastric acid to form a strong viscous gel, or alginate raft, which floats on the top of the gastric contents and effectively reduces by physical mechanism the reflux of the gastric contents into the oesophagus [9].…”
mentioning
confidence: 99%
“…raising the bed head during sleep) were published during the review period. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Impact on recommendations: None. Recommendation: The recommendation is unchanged with respect to the 2004 Consensus (see Table 2) 2.…”
Section: Diet and Lifestyle Changesmentioning
confidence: 99%